Healthcare workers' mobility from non-OECD countries to Portugal : a case-study approach - Bondar, Kateryna (2017)
Labor mobility has become one of the eventual consequences of globalization and economic integration. The continuous growth of globalization and the gap in terms of living standards between countries have resulted in the movement of professionals. The present research is aimed at adding new qualitative information about the pushing factors of medical labor mobility from non-OECD countries to OECD countries, and the choice of Portugal as a destination country. Using a case-study approach we identify factors that explain why Portugal is attractive for immigrants who have chosen it as a country to live and stay permanently. Identifying these factors may be useful for policy makers to define public policy instruments in order to attract highskilled workers.